2020
DOI: 10.1371/journal.pone.0229234
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of ten-year longitudinal changes in weight and waist circumference in the multi-ethnic rural Northern Norway. The SAMINOR Study, 2003-2014

Abstract: The obesity epidemic is dynamic with varying secular trends and differences between countries and ethnic groups. The objective of this study was to describe the age-and sex-specific longitudinal changes in weight and waist circumference in a rural Norwegian population with a high proportion of the indigenous Sami population. Based on two population-based surveys, SAMINOR 1 (2003-2004) and SAMINOR 2 (2012-2014), we present longitudinal changes in weight and waist circumference according to age at baseline in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
(92 reference statements)
2
5
0
1
Order By: Relevance
“…A large body of evidence suggests that weight, BMI, and WC increase throughout most of adult life [14][15][16][17], which is in line with our findings regarding the positive association of aging with obesity measures, observed in both genders. A prospective longitudinal study in Norway recently showed that mean weight in middle-aged men and women (aged 26-54 years) increased significantly during a 10-year follow-up while it reduced in elderly men and women (aged 60-69 years); however, mean WC increased throughout the follow up in all age groups [18]. The recent findings were completely in accordance with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…A large body of evidence suggests that weight, BMI, and WC increase throughout most of adult life [14][15][16][17], which is in line with our findings regarding the positive association of aging with obesity measures, observed in both genders. A prospective longitudinal study in Norway recently showed that mean weight in middle-aged men and women (aged 26-54 years) increased significantly during a 10-year follow-up while it reduced in elderly men and women (aged 60-69 years); however, mean WC increased throughout the follow up in all age groups [18]. The recent findings were completely in accordance with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In a 2020 study by Jacobsen et al [24], two populationbased investigations were joined, the first, SAMINOR 1 (2003-2004), and the second, SAMINOR 2 (2012-2014). A total of 3496 adults participated in both surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, not all secular changes associated with progress of civilisation are positive. Substantial increase in not only BMI, but also the prevalence of abdominal obesity as well as the intergenerational increase of waist circumference noted in the last decades in various populations are among examples of such changes (Arora et al, 2017; Dasgupta et al, 2008; Freedman et al, 2017; Jacobsen et al, 2020; Rerksuppaphol & Rerksuppaphol, 2014; Singhal et al, 2010; Suder et al, 2017; Zhai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%